Arthropod borne diseases in Italy: from a neglected matter to an emerging health problem - Roberto Romi (Istituto Superiore di Sanità, 2010)
In medical entomology, "Arthropod Borne Diseases", or "Vector Borne Diseases" (VBD) are intended as a group of human and animal infections caused by different pathogen organisms (protozoa, helminthes, bacteria and viruses) transmitted by the bite of a bloodsucking insect or arachnid. It is commonly known that the infectious diseases transmitted by Arthropods are mainly affecting tropical and subtropical countries, nevertheless some of them were or are still common also in the northern hemisphere, where they are usually maintained under control. VBD still represent some of the most important public health problems in the endemic areas but are becoming source of concern for developed countries too. Since the last decades of the past century, a number of VBD has been spreading geographically, being recorded for the first time in areas outside their original range. This phenomenon is strictly related to the peculiar epidemiological characteristics of these diseases, that are considered the most susceptible to climatic, environmental and socioeconomic changes. This article is a short overview of the VBD endemic and emerging in Italy. The possibility that some exotic vectors and/or pathogens could be introduced and become established in Italy is also discussed.